(untitled) (The Review of Diabetic Studies, 2024)
Intensive care units (ICUs) have a high risk of causing a healthcare-associated infection in a patient, and nursing staff members have a crucial role in preventing them. Nevertheless, there was no in-depth analysis of the factors that predetermined the adherence of the nurses to the infection control measures since the former research tended to analyze knowledge, practice, and contextual obstacles separately. This research paper was intended to perform a combined assessment of the ICU nursing staff involvement by conducting a simultaneous knowledge assessment, compliance assessment, and a perceived barriers assessment and facilitator assessment. The chosen method of study was a mixed-methods, cross-sectional study involving 120 nurses in two tertiary-care hospitals. Data were gathered using a knowledge questionnaire, which had been validated, a structured observational checklist, and in-depth interviews. Pearson correlation, t- tests, and multiple linear regression were applied in the analysis of quantitative data. The findings showed that there was a positive relationship between the knowledge scores and the compliance rate (r = 0.821, p < 0.001). Knowledge was reported to be the strongest predictor of compliance (R 2 = 0.758, p < 0.001, η² = 0.610, p < 0.001), and high workload (= -0.190, p = 0.034) and night shift duties (= -0.101, p = 0.034) were significant negative predictors in the regression model. Qualitatively, resource scarcity and excessive patient acuity were the most significant obstacles, and positive leadership and peer accountability were the most significant facilitators. This paper concludes that the implementation of infection control in ICUs needs more than just ongoing education, but the systemic measures that would cover both workload and resource-based issues, as well as shift-specific issues, to turn knowledge into a stable practice.